Reduced Recombination and Improved Performance of CdSe/CdTe Solar Cells due to Cu Migration Induced by Light Soaking - Jamarkattel, Manoj K; Mathew, Xavier; Phillips, Adam B; Bastola, Ebin; Subedi, Kamala Khanal; Alfadhili, Fadhil K; Abudulimu, Abasi; Friedl, Jared D; Awni, Rasha A; Li, Deng-Bing; Razooqi, Mohammed A; Koirala, Prakash; et al. (ACS applied materials & interfaces, 2022)
The performance of CdTe solar cells has advanced impressively in recent years with the incorporation of Se. Instabilities associated with light soaking and copper reorganization have been extensively examined for the previous generation of CdS/CdTe solar cells, but instabilities in Cu-doped Se-alloyed CdTe devices remain relatively unexplored. In this work, we fabricated a range of CdSe/CdTe solar cells by sputtering CdSe layers with thicknesses of 100, 120, 150, 180, and 200 nm on transparent oxide-coated glass and then depositing CdTe by close-spaced sublimation. After CdCl2 annealing, Cu-doping, and back metal deposition, a variety of analyses were performed both before and after light soaking to understand the changes in device performance. The device efficiency was degraded with light soaking in most cases, but devices fabricated with a CdSe layer thickness of 120 nm showed reasonably good efficiency initially (13.5%) and a dramatic improvement with light soaking (16.5%). The efficiency improvement is examined within the context of Cu ion reorganization that is well known for CdS/CdTe devices. Low-temperature photoluminescence data and V oc versus temperature measurements indicate a reduction in nonradiative recombination due to the passivation of defects and defect complexes in the graded CdSe x Te1–x layer.